Pengaruh Jumlah Input Dan Membership Function Fuzzy Logic Control Pada Robot Keseimbangan Beroda Dua - Indra Dwisaputra; Tareg Mahmoud; Meti Megayanti; Irvan Budiawan; Pranoto Hidaya R (Manutech : Jurnal Teknologi Manufaktur, 2016)
In this paper, a dynamic model of two-wheeled balancing robot has been created, and the two types of FLC has been designed. The Mamdani methods used on both FLC. The first FLC uses pendulum tilt angle theta (?) as the input and it requires the motor torque to keep the robot remains balanced as the output. The second FLC uses two inputs, the first input is theta (?) and the second input is the change in the value of theta (?) which is the output torque of the motor. The second plant model and FLC built by using Matlab Simulink. The first case is one input using 5 membership functions (mf). The second case is two inputs using the 5 and 7 mf. The characteristics and effects of the changes in the input and mf have been simulated in the Simulink and compared. By expanding the number of the inputs can reduce motor specification required in balancing robot. Meanwhile, by increasing the number mf, it can improve the performance of the controller much faster to reach the settling time.